Causal Linkage Between Inflammatory Bowel Disease and Primary Sclerosing Cholangitis: A Two-Sample Mendelian Randomization Analysis - Ying Xie; Xuejie Chen; Minzi Deng; Yuhao Sun; Xiaoyan Wang; Jie Chen; Changzheng Yuan; Therese Hesketh; Therese Hesketh (Frontiers in Genetics, 2021)
BackgroundObservational studies suggest an association between inflammatory bowel disease (IBD) [including ulcerative colitis (UC) and Crohn’s disease (CD)] and Primary sclerosing cholangitis (PSC), but the causal association between the two diseases remains unclear.MethodsWe used two-sample Mendelian randomization (MR) to estimate the causal association between IBD and PSC. We chose single nucleotide polymorphisms (SNPs) data for analysis, obtained from previous genome-wide association studies (GWASs). Pleiotropy, heterogeneity, and sensitivity analyses were performed for quality control.ResultsWe found that the causal associations between IBD (both UC and CD) and PSC were significant (e.g., IBD and PSC, Robust adjusted profile score (RAPS) OR = 1.29, 95% CI 1.16∼1.44, p< 0.01; UC and PSC, RAPS OR = 1.40, 95% CI 1.23∼1.58, p< 0.01; CD and PSC, RAPS OR = 1.13, 95% CI 1.02∼1.26, p = 0.02). MR Egger, IVW, and ML tests found statistical heterogeneity between determined IV estimates. The leave-one-out analysis also indicated the sensitivity of the SNPs (e.g., IBD and PSC, MR-Egger Q = 644.30, p< 0.01; UC and PSC, MR-Egger Q = 378.30, p< 0.01; UC and PSC, MR-Egger Q = 538.50, p < 0.01).ConclusionMR analyses support the positive causal effect of IBD (including UC and CD) on PSC in a European population. We provide suggestions for preventing and treating the two diseases.